Encyclopaedia of brewing - Boulton, Chris (Wiley-Blackwell, 2013)
"The only encyclopedia of its kind, Encyclopedia of Brewing provides a comprehensive description of terms which relate to the science and technology of beer, allied beverages, and the brewing and malting processes. The extensive and authoritative coverage provides an appropriately detailed description of each term under consideration, supplemented with diagrams and photographs where relevant. This essential first point of reference for information on brewing science offers commercial brewers and allied traders worldwide, as well as the burgeoning North American craft brewing sector, with an international perspective."--Resumé vydavatele
Keywords: pivo; pivovarnictví; beer; beer industry; encyklopedie; elektronické knihy; encyclopedias; electronic books